EFFECTIVENESS ANTI-INFLAMMATORY OF SUNGKAI LEAF (Peronema canescens Jack.) ETHANOL EXTRACT ON MALE RABBIT (Oryctolagus cuniculus) - Riana Versita; Aknes Dewi Setiani (Sekolah Tinggi Farmasi Muhammadiyah Cirebon, 2023)
Sungkai leaves are medicinal plants used empirically by the people of Bengkulu, often found in the tropical rainforests of Bengkulu province. Sungkai leaf secondary metabolites include flavonoids, alkaloids, saponins, and steroids/triterpenoids. Flavonoid compounds have hundreds of bioactivities including antipyretic, analgesic, antidiabetic, anticholesterol and anti-inflammatory. The aim of this study was to obtain a new drug that has effectiveness as an anti-inflammatory from ethanol extract of Sungkai leaves (Peronema canescens Jack) n male rabbits (Oryctolagus cuniculus) The study used an experimental method using male rabbits as experimental animals. The samples were divided into 5, namely negative control, positive control, and 2%, 4%, and 6% bioplacenton and sungkai leaf extract. Each group was subjected to 2nd degree burns.â€Measurements were taken every day for 8 days after injury. The results of the study proved that there was a decrease in wound diameter from Sungkai leaf extract, on average at a concentration of 2% it decreased by 64% and at a concentration of 66% it decreased by an average of 13.3% and at a concentration of 6% it decreased by an average of 78,67%. Based on the statistical results of the analisis of variance test, there is a significant difference. Keywords: Sungkai leaf extract, anti-inflammatory, Bioplacentone